2014
DOI: 10.1071/bt13232
|View full text |Cite
|
Sign up to set email alerts
|

Do habitat fragmentation and fire influence variation of plant species composition, structure and diversity within three regional ecosystems on the Sunshine Coast, Queensland, Australia?

Abstract: Abstract.Habitat fragmentation is considered to be one of the greatest threats to biodiversity. Species richness is predicted to decrease with decreasing patch size and increasing isolation, and this has been shown in some ecosystems. However, few studies have specifically investigated the effects of fragmentation on specific vegetation types, or compared different vegetation types within the same region. In this study, we assessed the influence of habitat fragmentation and time since fire on the floristic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
(112 reference statements)
0
4
0
Order By: Relevance
“…Our study compared biogeographical provinces (subregions) for their diversity so reduced the effect of one of these factors. Other studies of SE Queensland rainforest also found no significant relationship between diversity and habitat area [ 79 ]. Turner and Tjørve [ 78 ] suggest that habitat diversity influences species diversity at all spatial scales.…”
Section: Discussionmentioning
confidence: 91%
“…Our study compared biogeographical provinces (subregions) for their diversity so reduced the effect of one of these factors. Other studies of SE Queensland rainforest also found no significant relationship between diversity and habitat area [ 79 ]. Turner and Tjørve [ 78 ] suggest that habitat diversity influences species diversity at all spatial scales.…”
Section: Discussionmentioning
confidence: 91%
“…Inselberg floras are often reported as refuge areas for species unadapted to fire, and these findings support this concept (Heinze et al 1997;Lawler et al 1998;Hopper 2000;Hunter 2003bHunter , 2016. Species richness per plot (density) is often used as a surrogate for understanding the potential benefits of fire to the biodiversity of a community (Russell and Parsons 1978, Clarke 1988, Ross et al 2002, Etherington and Shapcott 2014. The results presented here would suggest caution in using richness per plot as a sole surrogate or reason to implement strategic fire on inselbergs.…”
Section: Discussionmentioning
confidence: 93%
“…The set of silica dried samples used for this study comprised 255 samples and 130 samples from other collections made from a variety of previous collections undertaken by the Shapcott lab and held at the University the Sunshine Coast [16,17,67]. DNA was extracted from 385 samples following the methods used by Shapcott [17].…”
Section: Dna Barcoding and Sequence Alignmentmentioning
confidence: 99%